(untitled) (Ustozlar uchun, 2025)
This article examines how the Industrial Revolution shaped the themes, characters, and social perspectives of Victorian literature. The Industrial Revolution, which began in the late eighteenth century, transformed England into an industrial power, bringing both progress and profound social disruption. Victorian writers such as Charles Dickens, Elizabeth Gaskell, Thomas Carlyle, and Charles Kingsley responded to these changes by portraying the struggles of the working class, the loss of rural traditions, and the moral challenges of modern capitalism. Their works reflected both the optimism of progress and the anxieties of inequality. The study argues that literature became a moral mirror of industrial society, revealing its human costs and ethical dilemmas